Gelar Karya Projek Penguatan Profil Pelajar Pancasila (P5) Kebekerjaan melalui kurikulum merdeka di SMKN 1 Cilegon - Shafa Yuniar Yasmin; Susilawati Susilawati; Muhamad Ryan Agustin; Intan Puspitasari; Ilham Akbar Darmawan (Pusat Riset dan Inovasi Nasional, 2023)
The learning process in the independent curriculum using the teaching factory learning method makes learning outcomes in vocational high schools relevant to producing students who are ready to work. The learning process is practical in order to produce products that can hone the skills possessed by each student. Learning with an approach like this will foster an entrepreneurial spirit in students. In the newest curriculum, namely the independent curriculum, the P5 project was created. In its implementation, P5 strengthens Pancasila values ​​with a project-based approach. This research uses descriptive qualitative methods with data collection techniques in the form of observation, literature study, documentation and evaluation. The implementation of the independent learning curriculum has been quite effective, especially when the implementation of P5 emerged.